Purple coneflower viruses: species diversity and harmfulness - Dunich, A.A.; Mishchenko, L.T. (2015)
Viral diseases became an actual problem in medicinal plants cultivation. The number of viruses known to infect purple coneflower increased significantly in the last years in many countries. However, there is no any review about the viral diseases of this valuable medicinal crop. Therefore, the aim of this article is to summarize the main information about the viruses affecting purple coneflower plants (Echinacea purpurea L. Moench.). An analysis of the literature data showed that purple coneflower could be infected by 10 viruses. These viruses belong to the families Bromoviridae, Bunyaviridae, Secoviridae, Potyviridae, Virgaviridae, and almost all of them are considered to be highly harmful plant viruses. Additionally, four of them (TMV, TSWV, CMV, PVY) are in the top 10 of the most economically important plant viruses in the world and occupy the first places. Such distribution and harmfulness of these viruses are explained by a wide range of sensitive host-plants, wild plants and weeds – reservoirs of an infection, and also a large number of vectors. The data from a few countries show that the viral diseases of purple coneflower are becoming more severe from year to year. The appearance of new viruses is registered on coneflower every year that complicates prognosis and risk estimation of epiphytoties in these regions which, for example, were revealed in Bulgaria, Lithuania and Ukraine. This review presents the detailed symptoms of the viral diseases in purple coneflower, the main properties of each virus and data about their harmful effect on the quality of raw material (the concentration of biologically active substances and heavy metals in plants).